Neighbourhood social fragmentation and the mental health of children in poverty. (January 2015) - Flouri, Eirini; Midouhas, Emily; Joshi, Heather; Sullivan, Alice
Abstract: Using data from 7, 776 Millennium Cohort Study children in England, we examined the role of neighbourhood social fragmentation in trajectories of emotional/behavioural problems at ages three, five and seven, and in moderating the association of children׳s emotional/behavioural problems with neighbourhood poverty, family poverty and adverse family events. Allowing for key background characteristics, social fragmentation generally added little to explain child outcomes, but there were fewer conduct problems among children in poor neighbourhoods with less fragmentation. Surprisingly, in less fragmented neighbourhoods poor families tended to feel less safe and more distressed, which was associated with children׳s conduct problems. Highlights: We tested neighbourhood social fragmentation (NSF) effects on child mental health NSF was generally unrelated to child mental health (at ages 3, 5, 7). Yet low NSF dampened the effect of neighbourhood poverty on antisocial behaviour. Poor families in less fragmented areas had children with more behaviour problems. This was because those families felt more distressed and unsafe in their locality.